Keanekaragaman Jenis Tumbuhan Dan Simpanan Karbon Pada Berbagai Tipe Penggunaan Lahan Di Kabupaten Pesisir Barat Provinsi Lampung - Dian Ariyanti; Nurheni Wijayanto; Iwan Hilwan (Jurnal Silvikultur Tropika, 2018)
Vegetation is one factor that can decrease carbon accumulation in the atmosphere. The diversity of plant species in each land use has different abilities to absorb carbon in the atmosphere. This research was conducted in Pesisir Barat Regency of Lampung Province on 4 (four) types of land use, namely: (1) natural forest in Balai Kencana Resort, Bukit Barisan National Park (2) oil palm plantation in Pekon Marang, (3) coffee plantation in Pekon Suka Mulya, and (4) agroforestry of repong damar in Pekon Pahmungan. This reserach aims to analyze the diversity of plant species and to calculate the potential of plant carbon stock and carbon sequestration (above ground biomass) using alometric equations in various types of land use in Pesisir Barat Regency. The research method was vegetation analysis to learn about the diversity of plant species and calculation of carbon stock using alometric equations. The results showed that the composition of plant species in Bukit Barisan NP found 83 plant species belonging to 37 families, in the palm plantation found 9 plant species belonging to 8 families, in the coffee garden found 17 plant species belonging to 11 families, and in agroforestry of repong damar found 73 plant species belonging to 33 families. The total carbon stock potential was 376.16 ton/ha and carbon sequestrated. 1 257.20 ton/ha with the highest carbon uptake available at repong damar agroforestry site of 901.11 ton/ha.Keywords: aboveground biomass, carbon, diversity, pesisir barat regency